Fungsi Media Digital pada Website Wisata Religi Berbasis Uses and Gratifications - Achmad Arrosyidi; Didiet Anindita Arnandy; Muhamad Basyrul Muvid (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Research on digital tourism communication remains dominated by discussions of social media, mobile applications, and online promotion, while the role of religious tourism websites in fulfilling users' informational, emotional, identity, social, tension-release, and spiritual needs has not been comprehensively explained. This limitation makes it difficult for destination managers to design websites that are not only informative but also capable of conveying religious meaning and experience. This study aims to analyze the functions of digital media in religious tourism websites through the Uses and Gratifications (U&G) perspective and to formulate an audience-gratification-oriented conceptual website model. The study employs a qualitative descriptive literature review of 16 scholarly sources published between 2007 and 2025, comprising journal articles and academic publications on digital tourism communication, religious tourism, website interactivity, user experience, and U&G theory. The data were analyzed through bibliographic classification, data extraction, content analysis, thematic coding, mapping onto cognitive, affective, personal identity, social integration, tension release, and spiritual dimensions, followed by theoretical interpretation and conceptual synthesis. The findings show that religious tourism websites function as information and educational hubs, promotional media, spaces for digital engagement, reinforcers of religious identity, and mediators of spiritual experience. The synthesis produces a model linking user motives, content, multimedia, navigation, and interactivity with audience gratifications, religious experience, satisfaction, engagement, and visit intention. Spiritual gratification emerges as a contextual extension of U&G theory in religious tourism communication